ADAPTASI KOMUNIKASI MASYARAKAT PENDATANG DI SLEMAN, YOGYAKARTA PASCA KONFLIK ETNIS BABARSARI “GOTHAM CITY” - Rezeki Amalia, Annisa; Rahardjo, Turnomo; Ratri Rahmiaji, Lintang (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2024)
The Babarsari “Gotham city” ethnic conflict was a conflict involving immigrant ethnic groups, mainly from Eastern Indonesia. The conflict created significant social tensions and affected interactions between local and migrant communities. It created social distance and increased negative stereotypes between the two groups of different ethnicities. As a result, migrants face challenges in adjusting to local norms and values. This then makes a new problem for other immigrant communities to adapt communication with local communities. This research aims to find out the communication adaptation process of immigrant communities in reducing concerns in the Babarsari “Gotham city” conflict by using descriptive qualitative research methods. The data collection technique used is in depth interview. The theories used in this research are integrative communication theory, communication accommodation theory, and adaptation interaction theory. The results of this study explain that the communication adaptation of migrant communities in Sleman, Yogyakarta after the Babarsari Ethnic Conflict “Gotham City” shows that changes in communication behavior by informants by actively participating in social and cultural activities that function as communication accommodation. The results of this study explained that the importance of communication accommodation theory in understanding the dynamics of interaction between immigrant and local communities after ethnic conflict occurred by strengthening social relations and creating harmony in the community.